Desenvolvendo habilidades de leitura crítica e reflexiva através do gênero multimodal meme sob a perspectiva dos multiletramentos - Andrade, Juliana Araújo de (2020)
One of the problems faced by teachers today concerns the students' growing lack of interest in the teaching-learning processes in the school context, but the resistance to reading activity is the aspect that most calls our attention, bearing in mind that, outside of school, students focus more on reading various contents that circulate on the internet, mainly in applications and social networks (such as Whatsapp and Facebook), which range from school research to memes. In view of this reality, it is essential that teachers seek to modify their methodology, paying attention to the multi-tools required by these new readings, made from contemporary texts, which are multimodal (ROJO, 2012), and which exert a certain fascination in these young people, mainly due to the use of multiple languages. In addition to this new context, part of our reality in the classroom is the low performance of students in the final years of elementary school, which belong to the school where we carry out our Professional Master's research (PROFLETRAS), in official tests that assess specific skills of textual understanding. Considering these factors, the general objective of this work was to develop an intervention proposal with the students, in order to enable the construction of critical and reflective reading skills. The specifics involved: holding reading workshops using memes as a multimodal genre, seeking to build the multi-tools required in view of new reading practices; relate other genres, such as short stories, news, poems, etc., to memes by thematic approach, aiming at expanding the students' cultural repertoire; evaluate the pertinence of the proposal development through the analysis of the results; and to highlight the importance of the school promoting the multi-elements required by the new reading and writing practices carried out by contemporary society. For this, we seek the support of authors who deal with Technology and Education: Gabriel (2013); Reading: Koch & Elias (2017), Lajolo (2011); Textual/discursive genre and multi-elements: Bakhtin (1997), Rojo (2013), Rojo & Barbosa (2015), Rojo & Moura (2012); Memes: Dawkins (1979), Recuero (2009), Fontanella (2009), Calixto (2017); among others, which theoretically support us. The present work is characterized, therefore, as action research of an interventional character, since it sought to combine theory and practice in solving a problem. In general, the actions focused on holding reading workshops with a 9th grade group of elementary school, in which memes, as a multimodal genre, and other genres, were read and critically analyzed, according to some descriptors used in Prova Brasil, selected from the 9th grade Portuguese Language Matrix. We also discuss racism, machismo and homophobia, in order to lead the student to reflect on these social issues that need to be tackled. The results show us that carrying out work aimed at deepening reading skills becomes effective, especially if planned around students' needs.